PERCEPTION OF SPIRITISM IN MUSLIM SOCIETY IN THE DIGITAL AGE (ANALYSIS OF SOCIAL ACTIONS BY MAX WEBER) - Ade Irma Gemilau; Nazzaruddin; Muhammad Nur; Dwi Fitri (Journal International Inspire Education Technology, 2026)
This study employs a qualitative approach with library research methods. Data analysis is conducted descriptively-analytically through stages of classifying, comparing, and interpreting literature findings using Max Weber’s social action theory framework. The research reveals that spiritist practices among Muslims cannot merely be viewed as deviations from religious teachings, but rather as expressions of social actions possessing subjective rationality for practitioners. From a Weberian perspective, these practices can be classified as instrumental-rational action, affective action, and traditional action, depending on motivations and surrounding social contexts. Digital age developments further drive transformations in spiritist practices via social media and online platforms, giving rise to new forms of charismatic authority and expanding their social legitimacy. This study concludes that the sustainability of spiritist practices reflects dynamic negotiations between formal religious doctrines, cultural traditions, and demands of digital modernity. This research aims to contribute to sociology of religion studies, particularly in understanding popular religious practices among Muslims through Max Weber’s social action theory.